Globalization, economic restructuring and competitiveness in the Metropolitan Area of Leon, Guanajuato, Mexico - Susana Suárez; Arlene Iskra Garcia (European Regional Science Association (ERSA), 2015)
Social and territorial spaces around the world are undergoing economic restructuring due to globalization process that has led to the removal of restrictions on capital mobility and the factors of production, and therefore, flows of capital, goods, technology, and especially the expansion of markets. This transnational reorganization of production and market globalization have led to the relocation of economic activity and spatial agglomerations. The relocation of production activities has generated local spaces acquire great importance, precisely because of the mobility and networking in the space of the different capitals: production, financial, human, and goods and information. Certainly globalization changes the spatial distribution of economic activity and accentuates socioeconomic differences among localities and regions, since they exhibit different rates of economic growth and social progress, because these spaces are not inserted in the same way, not to the same degree, in the new globalized economy. In this paper, the economic restructuring that has experienced the metropolitan area is analyzed in Metropolitan Area of León (MAL), Guanajuato, Mexico, in the last decade as a result of globalization especially productive restructuring and relocation of production activities by both TNCs and nationals enterprises. The MAL has become an area of attracting foreign direct investment, ie a 'growth pole', where the location of industrial activities is encouraged, and providing new investments, and the opportunity to exploit economies of scale reducing costs due to expansion and to merge with another companies. As a result has developed an economy called agglomeration geographic concentration of automakers and auto parts mainly in Silao, one of the municipalities that are part of the area. This agglomeration economy, has led to intense processes of competition between regions to attract investment, processes in which the State of Guanajuato has participated strongly and particularly MAL. The purpose of this paper is to examine the processes of economic restructuring of the area, and how has been developed the spatial and economic agglomeration, its impact on local economic growth, and competition generated between municipalities and other regions of the State of Guanajuato.
Keywords: 330; globalization; economic cluster; metropolitan area